2023
DOI: 10.3390/coatings13020342
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Oxidation of Enamel Coated Low-Alloyed Steel 16Mo3 in Water Vapor

Abstract: New types of ceramic coatings based on SiO2-Na2O-B2O3-TiO2 oxide phases were investigated as protection for boiler steel in power generation systems. Low-alloyed Cr-Mo 16Mo3 steel was coated with different compositions of enamel coatings to assess the protective potential of these coatings under water vapor at high temperatures. Oxidation at 650 °C for 50 h in Ar + water vapor was performed in a TGA apparatus to investigate the oxidation kinetics. The results indicate that the ceramic coatings provided a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The weight gain of coated sample is about 1 mg/cm2 compared to about 4 mg/cm2 for blank sample in TGA curve. This indicates that the ceramic coating is preventing oxidation of steel surface at high temperature of 500 ⸰ C (Boissonnet et al, 2023). On the basis of obtained data, it can be concluded that the ceramic coating improves the corrosion r resistant of mild steel sample.…”
Section: IIImentioning
confidence: 55%
“…The weight gain of coated sample is about 1 mg/cm2 compared to about 4 mg/cm2 for blank sample in TGA curve. This indicates that the ceramic coating is preventing oxidation of steel surface at high temperature of 500 ⸰ C (Boissonnet et al, 2023). On the basis of obtained data, it can be concluded that the ceramic coating improves the corrosion r resistant of mild steel sample.…”
Section: IIImentioning
confidence: 55%
“…This is obvious since the enamel coatings are already oxide-based glasses, and they would not be seriously affected by oxidation until softening at service temperatures. The enamels’ oxidation resistance in Ar/water vapour at 650°C was studied with promising results [59]; however, the further investigations with longer-time exposure considering possible enamel's hydrolysis issues, as conducted in the present work, should be required.…”
Section: Resultsmentioning
confidence: 99%